Bibliometric Exploration of Ethnomathematics: Trends, Characteristics, and Future Directions - Zea Zisman Usman; Ariyadi Wijaya (AL-ISHLAH: Jurnal Pendidikan, 2024)
Ethnomathematics plays a very important role in life, especially in mathematics learning. Even so, ethnomathematics is still rarely known to the public. As a result, ethnomathematics research is still rarely carried out. So, ethnomathematics is a good topic to discuss in research. But before that, do an analysis first. So, researchers conducted analytical ethnomathematics research using bibliometrics to explore publication characteristics, find trends, and find future research directions in the field of ethnomathematics. The data used is sourced from the Scopus database. The science mapping steps taken are study design, data collection, data analysis, data visualization, and interpretation. From the analysis, 580 documents were obtained that had been published from 1984 to 2023 with the core of the study being learners, mathematical concepts, learning mathematics and physics. Based on this information, it is clear that ethnomathematics still needs to be explored more deeply, considering that most documents are not articles. As for the characteristics of ethnomathematics research, apart from the lack of material in the form of articles, it turns out that ethnomathematics, which is currently developing, is a learning system in mathematics. Even ethnomathematics can improve high-order thinking skills (HOTS). Apart from that, research on teaching, design, and thinking processes in ethnomathematics is still small but very important. Based on this information, the most suitable novelty for future ethnomathematics research is research on the design of ethnomathematics-based mathematics learning models.